Teachers’ Perceptions in the Implementation of Text-Based Learning in Indonesian Secondary Education - Mayong Maman; Ramly Ramly; Muhammad Nur Ashar Asnur (International Journal of Language Education, 2023)
This study aimed to uncover the new evidence on how reform works based on Indonesian experience of adopting a text-based learning (TBL) approach in differing perceptions and teacher activities at the beginning of curriculum implementation. The secondary schools in Makassar city were used as the case studies while the study design had two questions. Data collection was conducted in two parts, A and B, which dealt with teachers' perceptions of TBL and the involvement at the beginning of its implementation, respectively. The samplecomprised 46 secondary school teachers from Makassar city, including 33 civil servants and 13 non-civil servants. These individuals had various teaching experiences in four categories, including 1 year or less, and more than 1 to 5, more than 5 to 10, and more than 10. Moreover, the collected data were analyzed using descriptive statistics. The results showed that the teacher's proportion with the same TBL perception in various aspects ranged from half to all. The proportion with the same activity was less than half of their number to nearly all of them. Generally, Indonesian secondary school teachers responded positively towardstext-based learning implementation.